The contribution of Ahlussunnah Waljamaah"s theology in establishing moderate Islam in Indonesia - Kanafi, Imam (HTS teologiese studies, 2021)
Radicalism and Islamic phobia have the potential to cause conflict amongst religious communities so that it needs social movements in building religious moderation. This study aims to understand and analyse the Ahlussunnah Waljamaah theology in the six largest Islamic community organisations in Indonesia in implementing religious moderation. This study uses a qualitative method with a phenomenological approach. Data obtained from interviews, observations and in-depth interviews regarding the process of externalising, objectifying and internalising the theology of Ahlusunnah Waljamaah in Nahdlatul Ulama, Rifa’iyah, Muhammadiyah, Al-Irsyad, Lembaga Dakwah Islam Indonesia and Front Pembela Islam organisations. Then, the data were analysed through social construction theory of Peter L. Berger and T. Luckman. The results show that the six largest Islamic community organisations in Indonesia apply Ahlussunnah Waljamaahs theology. Those Islamic community organisations differently understand the externalisation of Ahlussunnah Waljamaah theology based on its teaching. Thus, it has implications for Aswaja’s model of application (objectification) in the fields of state, preaching, social and cultural life. Aswaja’s internalisation is reflected in the moderate character of the figures and followers of mass organisations in Indonesia. The Islamic community organisations contribute to build Islamic moderation character by applying an established and consistent theology of Ahlussunnah Waljamaah in various fields.Contribution: This article provides insight into the contribution of Ahlussunnah Waljamaah’s theology in establishing moderate Islam in Indonesia. It contributes to build Islamic moderation’s character by applying an established and consistent theology of Ahlussunnah Waljamaah in various fields.